The Impact of the Covid-19 Pandemic on Incomes, Inequality and Poverty in the United Kingdom - Nicholas Sowels (Revue Française de Civilisation Britannique)
The Covid-19 pandemic swept across the world with incredible speed in early 2020, leading to lockdowns across the globe, and a huge collapse in output. The UK government, as elsewhere, stepped in rapidly and massively to support household incomes, most notably with the furlough scheme and an increase in benefits. As a result, household incomes were generally kept stable – and even increased for households with the least pay. This article sets out these policies and their consequences for incomes, poverty and inequality, before putting them into a longer-term context. It then moves on to examine how the expected fall in real incomes due to the surge in inflation since 2021, along with government policies announced in November 2022, will likely affect low-income households through to the middle of the decade.